Effect of Alirocumab Added to High-Intensity Statin on Platelet Reactivity and Noncoding RNAs in Patients with AMI: A Substudy of the PACMAN-AMI Trial - Ueki, Yasushi; Häner, Jonas D.; Losdat, Sylvain; Gargiulo, Giuseppe; Shibutani, Hiroki; Bär, Sarah; Otsuka, Tatsuhiko; Kavaliauskaite, Raminta; Mitter, Vera R.; Temperli, Fabrice; Spirk, David; Stortecky, Stefan; Siontis, George C. M.; Valgimigli, Marco; Windecker, Stephan; Gutmann, Clemens; Koskinas, Konstantinos C.; Mayr, Manuel; Räber, Lorenz (Thrombosis and Haemostasis, 2023)
Objective The effect of the PCSK9 (proprotein convertase subtilisin/kexin type 9) inhibitor alirocumab on platelet aggregation among patients with acute myocardial infarction (AMI) remains unknown. We aimed to explore the effect of alirocumab added to high-intensity statin therapy on P2Y12 reaction unit (PRU) among AMI patients receiving dual antiplatelet therapy (DAPT) with a potent P2Y12 inhibitor (ticagrelor or prasugrel). In addition, we assessed circulating platelet-derived noncoding RNAs (microRNAs and YRNAs).Methods This was a prespecified, powered, pharmacodynamic substudy of the PACMAN trial, a randomized, double-blind trial comparing biweekly alirocumab (150 mg) versus placebo in AMI patients undergoing percutaneous coronary intervention. Patients recruited at Bern University Hospital, receiving DAPT with a potent P2Y12 inhibitor, and adherent to the study drug (alirocumab or placebo) were analyzed for the current study. The primary endpoint was PRU at 4 weeks after study drug initiation as assessed by VerifyNow P2Y12 point-of-care assays.Results Among 139 randomized patients, the majority of patients received ticagrelor DAPT at 4 weeks (57 [86.4%] in the alirocumab group vs. 69 [94.5%] in the placebo group, p = 0.14). There were no significant differences in the primary endpoint PRU at 4 weeks between groups (12.5 [interquartile range, IQR: 27.0] vs. 19.0 [IQR: 30.0], p = 0.26). Consistent results were observed in 126 patients treated with ticagrelor (13.0 [IQR: 20.0] vs. 18.0 [IQR: 27.0], p = 0.28). Similarly, platelet-derived noncoding RNAs did not significantly differ between groups.Conclusion Among AMI patients receiving DAPT with a potent P2Y12 inhibitor, alirocumab had no significant effect on platelet reactivity as assessed by PRU and platelet-derived noncoding RNAs.
Keywords: acute myocardial infarction; percutaneous coronary intervention; platelet reactivity; proprotein convertase subtilisin/kexin type 9; microRNA